Analysis Factor Performance Nurse with Satisfaction Patient in Public Health Center Mejobo Kudus - Bahwono, Anggun; Yusianto, Wahyu; Prasetyo, Eko (Journal of Economics and Public Health, 2023)
Quality service health Good If performance nurse give guarantee quality service given health _ to patient good sick _ nor healthy . Performance nurse Good Good to patient , then patient so feel like And want to return Again as well as can recommend to family or his friend . This type of correlational research by using a cross sectional approach with a total sample of 4 5 people using a purposive sampling technique . The results of the study showed that most of the nurse's performance was good, as many as 29 respondents (64.4%) and the lowest nurse performance was less, as many as 5 respondents (11.1%) , patient satisfaction was partly 36 respondents (80.0%) were satisfied and 9 respondents (20.0%) were dissatisfied. There is a relationship between Nurse Performance and Patient Satisfaction at the Mejobo Kudus Health Center with a p value of 0.000. There is a relationship between Nurse Performance and Patient Satisfaction at the Mejobo Kudus Health Center with a p value of 0.000. expected nurse more increase performance so that treated patients _ feel more satisfied with services provided.